Poetic epistemologies and normalist teachers in the decolonial turn: Pedro Mariscal, Martin Adalberto Sánchez Huerta and Gloria Nahaivi reflect on the pandemic (2021)
Objective: This paper shows how three normalistas-educators -Pedro Mariscal, Martin Sánchez Huerta and Gloria Nahaivi- are providers of new knowledge in the decolonial turn through their poetic epistemologies in the context of the pandemic. Originality/support: This manuscript shows how teachers with their narratives contribute to the construction of decolonial epistemologies, especially in the context of the pandemic. This is significant because epistemologies have so far not taken into account teachers as providers of theoretical knowledge. Methods: This paper uses the methodology proposed by the philosopher Ramón Xirau to study the way in which poetic images are vehicles of theoretical knowledge and not only literary resources. Strategies/information gathering: the research work consisted of the study of primary sources such as original poems written by the normalistas-teachers as well as the consultation of their personal documentary archives. Conclusions: the decolonial perspective allows us to value the epistemic contribution of the normalistas-teachers addressed in this work if we identify the theoretical concepts contained in the poetic images of the poems they wrote. The findings show that the normalistas-teachers point out that Covid-19, besides being a health problem, has been a state of abandonment that has transformed loneliness into another demon that has no vaccine: a pandemic that has infected people with masks, which become silent tongues and walls of threads to form a world with a future that is not at all flattering, in other words, a dystopian world.